An analysis of the quality of educational services provided for rural administrators (A case study of Dehyars in Nasrabad District, Torbat Jam County) - hamdolah sojasi qedari; hamide mahmoodi; mahboobe shirmohamadi (تحقیقات کاربردی علوم جغرافیایی)
Training is one of the most convenient, and fastest ways to enable a society. Rural administrators are no exception; therefore, in order to achieve sustainable rural development, it is essential to enable Dehyars (rural administrators) through education and training courses. Accordingly, to improve Dehyar’s performance, they are provided with some training courses held by various organizations dealing with rural issues. Therefore, measuring the quality of training services is a prerequisite for improving the quality of training services and their performance. The research was conducted in a descriptive-analytic method. The population was comprised of all Dehyars in Nasrabad District, Torbat-e-Jam County. Nevertheless, due to small number of the participants, all Dehyars were included in the study. According to the results of the correlation test, both dimensions of ‘expectations’ and ‘perceptions’ have a positive and significant relationship with the individual characteristics of the Dehyars. The results of single sample t-test indicate that the mean of respondents' views in two dimensions of perceptions and expectations from training services is moderate to high. Further, according to the gap analysis (using the SERVQUAL model), in all aspects of the quality of training services, there is a negative gap between the perceptions and expectations of the Dehyars from training services. Nevertheless, the most important component which met the expectations of Dehyars about training services was related to accountability dimension; therefore, it is proposed to reduce the gap through organizing the workshops and training courses in an independent location with adequate equipment for the staff and instructors. It is also recommended to consult the Dehyars to see what courses they need.